2016
DOI: 10.1515/cclm-2015-1040
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about homocysteine and exercise? A review from the literature

Abstract: High total homocysteine (tHcy) concentrations contribute to an increased risk of cardiovascular diseases and neurodegenerative disorders. Several investigations have focused on the effect of exercise on tHcy concentrations, but results remain controversial. The differences among the methodologies in the investigations make difficult the interpretation of results. This review differentiates the effects of exercise on tHcy and establishes the relation with the implicated biomarkers on tHcy metabolism related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…Souza-Silva and Gonçalves da Mota (2014) in a recent revision asserted that it would be prudent to discern the types of exercise that reduce homocysteine levels and therefore potentially reduce the risk of blood vessel damage. According to these authors, and others (Maroto-Sánchez et al 2016), homocysteine was lower in patients with the greatest amount of daily physical activity.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Souza-Silva and Gonçalves da Mota (2014) in a recent revision asserted that it would be prudent to discern the types of exercise that reduce homocysteine levels and therefore potentially reduce the risk of blood vessel damage. According to these authors, and others (Maroto-Sánchez et al 2016), homocysteine was lower in patients with the greatest amount of daily physical activity.…”
Section: Discussionmentioning
confidence: 69%
“…However, the impact of exercise on tHcy remains unclear. A recent review (Maroto-Sánchez et al 2016) identifies that acute exercise induces increases in tHcy. However, no consensus exists regarding chronic exercise due to a large variety of exercise interventions, with different intensities, duration and mode of exercise.…”
mentioning
confidence: 99%
“…Several studies showed a higher incidence of HHcy in elite athletes compared with sedentary subjects, likely due to an increased consumption of SAM required for creatine synthesis during strenuous exercise, and creatine phosphate, as well as increased protein turnover [3,10,26]. Hcy increases in elite athletes may represent a relevant health issue, given the reported key role for HHcy as a contributor to early and advanced stages of CVD [6,15].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that strenuous physical activity is associated with the development of hyperhomocysteinemia (HHcy) [3,19,26], a condition, characterized by the increase of homocysteine (Hcy) plasma levels above normal reference values, that is a well-recognized risk factor for CVD [6,15]. Indeed, Hcy contributes to the development of CVD by several different mechanisms, such…”
Section: Introductionmentioning
confidence: 99%
“…A possible neurobiological mechanism that elucidates, at least partly, the effects of resistance training on white matter and cognition could be derived from the known effects of resistance training on the amino acid homocysteine. First, it is important to remember that a higher total homocysteine level is linked to (i) a higher extent of white matter lesions [334], (ii) a higher (faster) brain atrophy rate [335][336][337], (iii) an increased risk of neurological diseases [338][339][340][341][342][343][344], and (iv) poorer global cognitive performance and executive functioning [345][346][347][348][349][350]. Second, it is known that resistance training decreases the level of plasma [351] and serum homocysteine [187,352].…”
Section: Homocysteinementioning
confidence: 99%